Development of Science Process Skills-Based Student Worksheets on Renewable Energy Materials to Enhance Mutual Cooperation and Creative Character - Maimunah, Siti; Suyidno, Suyidno; Mahtari, Saiyidah (Jurnal Ilmiah Pendidikan Fisika, 2025)
Science process skills are an approach that should be used as a reference by educators in carrying out good physics learning in the classroom. This research aimed to produce valid and practical science process skills-based renewable energy material student worksheets to improve mutual cooperation and creative characters. The type of research conducted is 4D model development research. The research trial subjects were 33 students of class X MA. Data collection techniques used validation instruments for validity and student response questionnaires for practicality. The study results are: (1) student worksheets are categorized as very valid with an average score of 3.52; (2) student worksheets are categorized as practical with an average score of 2.64. Thus, the worksheet on renewable energy material based on science process skills is feasible to improve the character of mutual cooperation and creative and cognitive abilities of students in physics learning.